Nonuniform Corrosion in the Vertical Direction of Q345 Steel in a Real Ocean Environment - Jiezhen Hu; Huan Huang; Xin Hu; Peichang Deng; Guo Zheng; Jiahong Chen; Zhiwen Tu (Journal of Chemistry)
The aim of this investigation was to study nonuniform corrosion in the vertical direction of Q345 steel in the South China Sea. First, a metal corrosion monitoring system was designed and applied based on the coulometer principle and array electrode technology. Then, through coulometer testing, weightlessness analysis, electrochemical testing, and surface morphology observation, the corrosion behavior of Q345 steel used in an offshore wind turbine in Zhanjiang Bay in the South China Sea was studied. The results revealed that within the first 30 days of the experiment, the array electrodes connected by electricity exhibited sacrificial anode/cathode protection with self-coupling. Therefore, the corrosion rates of the electrodes were slowed. Between 60 and 120 days, the array electrodes underwent a transition in the anode/cathode region. In actual marine environments, the most severely corroded areas of long metal structures were near the sea surface and seabed and had to be prioritized for protection.